Preparation, Characterization, and Activity Evaluation of CuO/F-TiO2 Photocatalyst - Zhang Jinfeng; Yang Yunguang; Liu Wei (International Journal of Photoenergy)
CuO/F-TiO2 nanoparticle photocatalyst was prepared by ball milling. The photocatalyst was characterized by X-ray powder diffraction, scanning electron microscopy, transmission electron microscopy, UV-Vis diffuse reflectance spectroscopy, and photoluminescence emission spectroscopy. The photocatalytic activity was evaluated by photocatalytic oxidation of rhodamine B and reduction of Cr2O7 2−. The results showed that, for F-TiO2 photocatalyst, the photooxidation activity increases remarkably with the increasing amount of NH4F up to 1.0 g, and the photoreduction activity decreases gradually with the increase in the amounts of NH4F. For the CuO/F-TiO2 photocatalyst, the photoreduction activity increases greatly with the increase in the amount of doped p-CuO up to 1.0 wt.%, and the photooxidation activity decreases rapidly with the increase in the amounts of doped p-CuO. Compared with pure TiO2, the photoabsorption wavelength range of the CuO/F-TiO2 and F-TiO2 photocatalysts red shifts and improves the utilization of the total spectrum. The effect of ball milling time on the photocatalytic activity of the photocatalysts was also investigated. The mechanisms of influence on the photocatalytic activity of the photocatalysts were also discussed.